Chitin nanofiber-coated biodegradable polymer microparticles via one-pot aqueous process. (15th July 2023) - Kaku, Yuto; Isobe, Noriyuki; Ogawa, Nanako O.; Ohkouchi, Naohiko; Ikuta, Tetsuro; Saito, Tsuguyuki; Fujisawa, Shuji
Abstract: Tailoring the surface of biodegradable microparticles is important for various applications in the fields of cosmetics, biotechnology, and drug delivery. Chitin nanofibers (ChNFs) are one of the promising materials for surface tailoring owing to its functionality, such as biocompatibility and antibiotic properties. Here, we show biodegradable polymer microparticles densely coated with ChNFs. Cellulose acetate (CA) was used as the core material in this study, and ChNF coating was successfully carried out via a one-pot aqueous process. The average particle size of the ChNF-coated CA microparticles was approximately 6 μm, and the coating procedure had little effect on the size or shape of the original CA microparticles. The ChNF-coated CA microparticles comprised 0.2–0.4 wt% of the thin surface ChNF layers. Owing to the surface cationic ChNFs, the ζ-potential value of the ChNF-coated microparticles was +27.4 mV. The surface ChNF layer efficiently adsorbed anionic dye molecules, and repeatable adsorption/desorption behavior was exhibited owing to the coating stability of the surface ChNFs. The ChNF coating in this study was a facile aqueous process and was applicable to CA-based materials of various sizes and shapes. This versatility will open new possibilities for future biodegradable polymer materials that satisfy the increasing demand for sustainable development. Graphical abstract: Unlabelled Image